2018
DOI: 10.3324/haematol.2018.195131
|View full text |Cite
|
Sign up to set email alerts
|

miR-497 suppresses cycle progression through an axis involving CDK6 in ALK-positive cells

Abstract: Anaplastic large-cell lymphoma, a T-cell neoplasm, is primarily a pediatric disease. Seventy-five percent of pediatric anaplastic large-cell lymphoma cases harbor the chromosomal translocation t(2;5)(p23;q35) leading to the ectopic expression of NPM-ALK, a chimeric tyrosine kinase. NPM-ALK consists of an N-terminal nucleophosmin (NPM) domain fused to an anaplastic lymphoma kinase (ALK) cytoplasmic domain. Pediatric NPM-ALK+ anaplastic large-cell lymphoma is often a disseminated disease and young patients are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…When treating cervical cancer cells with miR-497-5p inhibitor, we found that CBX4 gene expression was increased, cell proliferation rate of cervical cancer cells was elevated, and cell cycle was arrested at S-phase, which is consistent with the regulatory effect of miR-497-5p on the cell cycle of ALK-positive cells, melanoma cells and 293T cells. [34][35][36] However, inhibition of miR-497-5p together with down-regulation of CBX4 resulted in decreased proliferation of cervical cancer cells. The number of S-phase cells in this group was lower than that of cells with inhibition of miR-497-5p, and higher than that of control group, suggesting that CBX4 is a key molecule in the regulation of the growth of cervical cancer cells by miR-497-5p, and changes in CBX4 expression directly affect the proliferation of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…When treating cervical cancer cells with miR-497-5p inhibitor, we found that CBX4 gene expression was increased, cell proliferation rate of cervical cancer cells was elevated, and cell cycle was arrested at S-phase, which is consistent with the regulatory effect of miR-497-5p on the cell cycle of ALK-positive cells, melanoma cells and 293T cells. [34][35][36] However, inhibition of miR-497-5p together with down-regulation of CBX4 resulted in decreased proliferation of cervical cancer cells. The number of S-phase cells in this group was lower than that of cells with inhibition of miR-497-5p, and higher than that of control group, suggesting that CBX4 is a key molecule in the regulation of the growth of cervical cancer cells by miR-497-5p, and changes in CBX4 expression directly affect the proliferation of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In an NHL case–control population, Alan Fu et al demonstrated that reduced levels of mature miR-618 may lead to the deregulation of the targeted genes HAT1/HDAC3. The inactivation of miR-497 in human NPM-ALK ( +) anaplastic large-cell lymphoma cells promotes cell growth by dysregulating targeted CDK6, E2F3, and CCNE1, the three regulators of the G1 phase of the cell cycle [ 151 ]. These findings suggest that some miRNA genes are controlled by epigenetic alterations in their promoter regions and can be activated by inhibitors of DNA methylation and HDAC.…”
Section: Noncoding Rnas Regulate Peripheral T-cell Lymphoma: the Rolementioning
confidence: 99%
“…cancer (44,45), thyroid cancer (46,47), cutaneous squamous cell carcinoma (48,49), melanoma (50), glioma (51), clear cell renal cell carcinoma (52), anaplastic large cell lymphoma (53), esophageal carcinoma (54) and bladder cancer (9), among others. These results suggest that miR-497 acts as a tumor suppressor.…”
Section: Regulation Of Microrna-497 Expression In Human Cancer (Review)mentioning
confidence: 99%